243142 - .f(x,y)=x ln(y cos x =x*d/dx ln(y cosx ln(y cos x...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
14.2 d/dx of (xe^SQ(XY)) ==x[e^(xy) d/dx (Sq(xy))]+e^(SQ(xy)) ==x[e^(SQ(xy))* ((1/(2*(SQ(xy))*y]+e^(Sq(xy)) =====e^(SQ(xy)) *[xy/(2*(SQ(xy))+1] d/dvo of (vo+at)===ANS=1 t=2pir/v ……d/dr = 2pi/v* d/dr(r)…….2pi/v*1=2pi/V df/dx (Lim pi/3,1)….
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: .f(x,y)=x ln (y cos x) =x*d/dx ln(y cosx) + ln (y cos x) d/dx (x) =x*1/(y cos x)*d/dx (y cos x) + ln (y cos x) d/dx (x) =x* 1/(y cos x) *(-y sin x) + ln (y cos x) =-x tan x + ln (y cos x) NOW plug in Variables ==-2.51...
View Full Document

This note was uploaded on 03/21/2011 for the course MTH 243 taught by Professor Barabara during the Spring '11 term at Rhode Island.

Ask a homework question - tutors are online